Interdisciplinary Approach for Sustainable Forest Management - Ivanova, Natalya Sergeevna (International Journal of Bio-resource and Stress Management, 2018)
The possibilities of the Catastrophe Theory for predicting the dynamics of forest ecosystems and developing scenarios for sustainable forest management are discussed. The main features of the approach are described. The achievements and difficulties of application for the Catastrophe Theory in scientific research have been discussed. Examples are given of the application for the study of ecotones (steppe - forest), succession modeling, forest restoration prediction and forest description as a multilayer system. Particular attention is paid to the problem of reforestation. The Catastrophe Theory can provide an explanation for the appearance of abrupt changes in reforestation as a result of minor changes in controlling factors and why such changes occur in different configurations of control factors. Methods of Catastrophe Theory allow, identifying and predicting crises in the forest development, which is very important for the management of bioresources. A great achievement of modern Catastrophe Theory is the transition from qualitative forecasting of generalized situations to quantitative prediction of real situations. Modern models, built on its basis and parameterized using field observations, describe real situations quantitatively. These models can be used to assess whether the trajectory is following the desired path and to estimate recovery rate or to forecasting possible scenarios. The methods of Catastrophe Theory are universal and can be used for all forests of the world and other ecosystems.